Culturally Relevant Approaches: Towards Reducing Equity Gaps at a Hispanic-Serving Institution in the Apparel Major: Culturally Relevant Approaches Apparel - Trejo, Helen; Whang, Claire; Canedo, JC (Educational (Re)naissance, 2026)
This pilot study was developed to learn more about Apparel students and support their success based on primary challenges identified with equity gaps among Under-Represented Minority (URM) students who are Hispanic, Black, and/or Indigenous. This pilot study was developed to learn more about Apparel URM students and support their success. We took practitioner-scholar approaches to apply Culturally Relevant Pedagogy (CRP) with students and faculty. The objectives were: (1) to identify Culturally Relevant (CR) perspectives of Apparel students, including their motivations, barriers, and recommendations; (2) to intentionally engage with students and faculty to improve a sense of achievement, excellence, and student-teacher relationships; and (3) to strategically implement CR approaches with undergraduates in the Apparel major. Research methods included student focus group interviews, and surveys based on project activities that included hosting a faculty workshop and supplemental instruction. This study conveys the feasibility of integrating CR approaches in Apparel practice-based approaches to support students and begin to address equity gap issues.